Foam Chuck Glider: Sarana Pelatihan untuk Meningkatkan Jiwa Kewirausahaan Karang Taruna - Junaidin, Buyung; Wahju Santoso , Djarot; Sudibya, Bambang (Universitas Mataram, 2024)
Entrepreneurship is one of the main focuses of Karang Taruna’s activities in an effort to improve community welfare. Karang Taruna in Jaden Village, Mranggen, Jatinom, Klaten, offers a variety of programs that the community can participate in. However, aeromodeling has not yet been included as part of the development activities in Karang Taruna of Jaden Village, Mranggen, Jatinom, Klaten, due to a lack of knowledge and information about aeromodeling, even though Klaten is very close to the Adisutjipto Airport and the Indonesian Air Force Base, both of which frequently hold aeromodelling events and activities. A training program on making simple aeromodelling planes, such as foam chuck gliders, could become a source of independence and a foundation for further understanding of aeromodelling, which has the potential to develop into a wider business field. In this training, the OID (Observe-Imitate-Do) method is applied to accelerate and strengthen the learning process. The results of the training demonstrate the effectiveness of the activity through indicators such as: participants showing great enthusiasm in following the entire program, as evidenced by their active participation and high level of involvement in all activities, the application of the OID method providing effective and comprehensive learning experiences for the participants, and the training successfully sparking participants’ interest in exploring entrepreneurship.